Studi Etnografi dalam Penelitian Bimbingan dan Konseling - Ghina Hanifah; Nasibah Huriyyatul Jannah; Salsabila Azahra; Vania Naswa Aulia Rahman; Salma Ariza Putri; Ahman Ahman (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to examine the application of ethnographic studies in multicultural guidance and counseling research. The background of the study is based on the importance of a deep understanding of culture in counseling practice, considering Indonesia's high cultural diversity. Ethnography was chosen as an approach due to its ability to holistically explore cultural dynamics through participatory observation, in-depth interviews, and analysis of cultural artifacts. The method used is a literature review, analyzing various sources such as articles, books, and previous research. The findings indicate that the ethnographic approach enables counselors to gain a deeper understanding of clients' cultural values, making counseling services more sensitive and effective. The implications of this study highlight the need for developing cultural literacy training for counselors and creating culturally based counseling guidelines to support inclusive and relevant counseling practices in multicultural societies.